A biographic approach to the study of biocultural learning - Garavito-Bermudez, Diana (Adult Education Discourses, 2020)
Natural environments such as arable lands, lakes, the sea, forests and savannahs are not only places for living and supporting the livelihoods of people, they constitute contexts of significance for sustainability. On the one hand, the study of the knowledge that people generate about their local natural environments has mainly been characterised by romantic views and false assumptions of learning, and more specifically knowledge generation (acquisition), as a merely social or collective process within social-ecological systems literature. It has led to unequal power relationships between different types of knowledge (scientific and experiential) as they were totally separated in human cognition development and structure, and professional knowledge and practices. On the other hand, there is limited interest in the study of professional learning among local communities having natural environments as their living and workplaces within adult educational research. Based on the empirical study of Swedish fishers and farmers, this article contributes to further development of approaches and methods for the understanding of biocultural learning or professional learning in and about nature. It answers the research questions of how the study of biocultural learning benefits from using a biographical approach and a variety of data collection methods, and how individual and social circumstances impact biocultural learning. Findings contrast the previous research literature on local ecological knowledge, and lead to reflections about the role of adult education research for the development of theories and methods for sustainability research and practices.